Role of Flow Simulation as a Tools for Failure Analysis Induced by Sulphate-Reducing Bacterial - Yudha Pratesa; Badrul Munir (EPI International Journal of Engineering, 2018)
Sulphate Reducing Bacterials (SRB) is one of the challanging problem in oil and gas. It could attack the metals to form a pit. The SRB ussually left a colony as the indication of corrosion attack. One of the main problem to prevent the corrosion attack is the ablitity to mapping the possibility of attacking area. However, this study offer a method to simulate the bacterial growth area based on the differential flow rate in the pipe. The flow simulation showed the ability to be used as the analytical tool for the bacterial growth mappings. Laboratory testing was also conducted for confirmation of the SRB presence in the system